Apoptosis in C. elegans - Hengartner, Michael (Henry Stewart Talks, 2007)
Programmed cell death in C. elegans during development and adulthood, Differentiation, The genetic pathway for programmed cell death, ced-3, ced-4 and ced-9, Activation of the cell death machinery during C. elegans development and in C. elegans vs. mammals, How does C. elegans regulate activation of the apoptosome?, Cell death specification (ces) genes, NSM sister cell death, Transcription factors, A model for C. elegans DNA damage response, gla-3, A molecular model for the recognition and removal of apoptotic cells in C. elegans